2017
DOI: 10.1080/09273948.2017.1319959
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Depression and Anxiety in Patients with Active Uveitis

Abstract: A positive screening test for depression and anxiety is common in patients with uveitis. Low vision and panuveitis are associated with depression. Depression is associated with impairment of VR-QOL and HR-QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 32 publications
2
32
1
Order By: Relevance
“…In line with our findings, Augustin et al did not find evidence for anxiety disorder in patients with age-related macular degeneration [31]. Moreover, Onal et al found that 52.5% patients with uveitis screened for symptoms of anxiety were younger (Mean age: 31.5 vs. 40 years, p = 0.009) and had earlier onset of uveitis (Mean age: 26 vs. 35 years, p = 0.015) [17]. Since the mean age of the patients in this study was approximately 62 years, age might contribute to the missing significance of symptoms of anxiety in the disease group.…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our findings, Augustin et al did not find evidence for anxiety disorder in patients with age-related macular degeneration [31]. Moreover, Onal et al found that 52.5% patients with uveitis screened for symptoms of anxiety were younger (Mean age: 31.5 vs. 40 years, p = 0.009) and had earlier onset of uveitis (Mean age: 26 vs. 35 years, p = 0.015) [17]. Since the mean age of the patients in this study was approximately 62 years, age might contribute to the missing significance of symptoms of anxiety in the disease group.…”
Section: Plos Onesupporting
confidence: 89%
“…Depression and anxiety have been determined as significant comorbidities among patients with severe ocular conditions such as glaucoma, age-related macular degeneration, and retinitis pigmentosa [14][15][16]. But there have been only limited reports on screening for psychological alterations in patients with uveitis [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The MOS 36-item short form health survey (SF-36) has been used world-wide as a generic and coherent measure to assess HRQoL in patients and residents [8][9][10]. More than 40 translated versions have been applied around the world [11] and it is the standard for international quality of life assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported on the quality of life aspects tied to the difficulties of performing daily tasks and social functioning associated with RP. [11][12][13] Another important component included in quality of life is mental health, because a diagnosis such as anxiety or depression has been shown to have negative implications. 14,15 Higher levels of anxiety and depression have shown to be associated with various ocular pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma, for example, was found to have a dramatic increase for comorbid anxiety and depression. [9][10][11][12][13][14][15] In a Japanese study comparing glaucoma and RP, patients with RP were found to have a higher prevalence of depression. 16 The higher prevalence compared with patients with glaucoma, for whom reported odds ratios (ORs) were as high as 10.6 for anxiety and 12.3 for depression vs those without glaucoma, shows the importance of investigating the relationship for patients with RP.…”
Section: Introductionmentioning
confidence: 99%